Monetary Rules for Emerging Market Economies - Rebucci, Alessandro (IMF Working Papers; Working Paper, 2002)
We compare the performance of a currency board, inflation targeting, and dollarization in a small, open developing economy with a liberalized capital account. We focus on the transmission of shocks to currency and country risk premia and on the role of fluctuations in premia in the propagation of other shocks. We calibrate our model on Argentina. The framework matches the second moments of key variables well. Welfare analysis suggests that dollarization is preferable to alternative regimes because it removes currency premium volatility. However, a currency board can match dollarization on welfare grounds if the central bank holds a sufficiently large stock of foreign reserves.